2019
DOI: 10.1055/a-0833-8313
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Levels of Serum Insulin-like Growth Factor I and Functional Recovery, Mortality, and Recurrent Stroke at a 7-year Follow-up

Abstract: Background The association of serum insulin-like growth factor I (s-IGF-I) with favorable outcome after ischemic stroke (IS) beyond 2 years is unknown. We investigated whether the levels of s-IGF-I 3 months post-stroke were associated with functional recovery up to 7 years after IS, considering also mortality and recurrent strokes. Methods Patients (N=324; 65% males; mean age, 55 years) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Moreover several studies have suggested that Alzheimer’s Disease is marked by an increased resistance to IGF‐1 (Moloney et al, ; Talbot et al, ), which emphasizes the importance for examining the effects of reduced IGF‐1 signaling in the adult brain. Clinical trials have yet to show efficacy of exogenous IGF‐1 treatment in humans; however, evidence shows a strong inverse relationship between IGF‐1 levels and the risk/severity of many of these excitotoxic diseases in humans (Aleman et al, ; Dong, Chang, Ji, Tao, and Wang, ; Tumati, Burger, Martens, Van Der Schouw, and Aleman, ; Aberg et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover several studies have suggested that Alzheimer’s Disease is marked by an increased resistance to IGF‐1 (Moloney et al, ; Talbot et al, ), which emphasizes the importance for examining the effects of reduced IGF‐1 signaling in the adult brain. Clinical trials have yet to show efficacy of exogenous IGF‐1 treatment in humans; however, evidence shows a strong inverse relationship between IGF‐1 levels and the risk/severity of many of these excitotoxic diseases in humans (Aleman et al, ; Dong, Chang, Ji, Tao, and Wang, ; Tumati, Burger, Martens, Van Der Schouw, and Aleman, ; Aberg et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…38 A recent study indicated that within chronic ischemic stroke survivors, the levels of IGF-1 in circulation 3 months following insult were not associated with changes in mortality 7 years later, nor were they associated with increased risk of recurrent stroke. 39 Thus, while IGF-1 levels prior to, or at the time of ischemic insult may influence mortality, the levels present within circulation several months following insult may not.…”
Section: Clinical Connections Between Igf-1 and Ischemic Strokementioning
confidence: 99%
“…44 Follow-up studies at 2 and 7 years indicate a much subtler change in outcome. 39,45 Interestingly, the beneficial effects of physical exercise on cognition in chronic stroke patients are also accompanied by higher circulating IGF-1, suggesting that effective interventions are also marked by increased IGF-1 signaling. 46 On the other hand, Armbrust et al observed more favorable mRS scores in acute stroke patients when IGF-1 levels following insult were low 8 days after insult.…”
Section: Clinical Connections Between Igf-1 and Ischemic Strokementioning
confidence: 99%
“…However, the role of circulating IGF-I and its associations with functional outcome in human stroke appear to be complex. While high serum levels of IGF-I have been associated with both worse outcomes ( 123 , 124 ) and greater stroke severities, they are also linked to better long-term recovery ( 85 , 125 ). These discrepancies can partially be explained or confounded by the fact that the levels of serum IGF-I are lower in aged, malnourished, and/or sedentary subjects ( 71 ) and may depend on the post-stroke sampling time-point, as suggested previously ( 122 ).…”
Section: Gh/igf-i and Various Brain Diseases In Relation To Hbmentioning
confidence: 99%
“…Although the absolute levels of serum IGF-I appear to predict functional outcome, post-stroke dynamic changes (decreases) in the levels of serum IGF-I may also be at least as important (122,126). Some studies have shown a weak-to-moderate correlation between serum IGF-I and Hb (64,65,68), a relationship that has not been investigated in other studies (85,122,125). That the functional outcome of stroke seems to be dependent upon the status of the GH/IGF-I axis indicates that there is a correlation with Hb, and this aspect deserves further investigation.…”
Section: Stroke and Hemoglobinmentioning
confidence: 99%